2020
DOI: 10.1155/2020/8569314
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reaction Reporting in Ethiopia: Systematic Review

Abstract: Adverse drug reactions are major global public health problems and an important cause of mortality. Problems related to medicines safety can emerge from real-life medication use due to increasing access to complex treatment of concomitant infectious and noncommunicable diseases, hence leading to a higher prevalence of drug-related problems. The objective of this review was to assess the knowledge, attitude, and practice of adverse drug reaction reporting among health care professionals in Ethiopia. Relevant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…5 However, these secondline drugs tend to be toxic and their longer duration of use predisposes patients to adverse drug reactions (ADRs). 6 Until 2015, treatment of MDR-TB involved the use of more toxic and longer duration (20)(21)(22) regimens in Uganda. 7,8 However, the introduction of shorter duration (9-12 months) and more tolerable regimens has redefined clinical research and management of MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 However, these secondline drugs tend to be toxic and their longer duration of use predisposes patients to adverse drug reactions (ADRs). 6 Until 2015, treatment of MDR-TB involved the use of more toxic and longer duration (20)(21)(22) regimens in Uganda. 7,8 However, the introduction of shorter duration (9-12 months) and more tolerable regimens has redefined clinical research and management of MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…12,20 In addition to the disruption of therapy in terms of compliance, ADRs are also associated with other negative outcomes including increased length of hospital stay and severe illness. 5,21 Given the scantiness of data about ADRs among patients receiving MDR-TB treatment and changes in local patterns of TB and MDR-TB prevalence in Uganda, this study aimed to assess the prevalence, types, and factors associated with ADRs among patients receiving MDR-TB treatment at Mbarara Regional Referral Hospital (MRRH), in southwestern Uganda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporting ADR is a breach of patient confidentiality, Reporting creates an additional workload and a lacks of motivation for reporting was also believed to be reasons for not reporting by 12.6%,47%), and 36.3% of the respondents, respectively. These reasons are found to be in common in the findings of the study conducted at public hospitals of Ethiopia (19). Assessment of ADR reporting practice determinants indicated that only being a druggist and pharmacy technician was a significant determinant of ADR reporting practice.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, a systematic review in India reported that 55.6% of the health professionals were not aware of the national pharmacovigilance program [ 53 ]. In another systematic review in Ethiopia, 45.9% of health professionals were aware of the national ADR reporting system and their knowledge of ADR was determined (41.5%) [ 54 ]. Therefore, it seems that healthcare authorities should increase nurses' knowledge about the PV system and also facilitate nurses' awareness of ADR reporting form by adopting appropriate strategies.…”
Section: Discussionmentioning
confidence: 99%